Pause duration of disfluent speech - Teixeira, João Paulo (2014)
This work has the goal of comparing the pause duration in the disfluent speech and normal speech. Disfluency and normal spontaneous speech was recorded in a context were the subjects had to describe a scene from each other. The pause determination algorithm is presented. The automatic pause determinations allowed the measure of percentage of silence along the record of several minutes of speech. The stuttering scale is used to compare the severity of the subject. As expected, the percentage of speech pauses parameters is rather different in subjects with and without disfluent speech, but it does not seem that it is proportional to the severity of the disfluency.